Prevalence of Developmental Delay and Factors Affecting the Development Status among Under 5 Children in an Urban Slum of Agra City - Agarwal, Disha; Chaudhary, Shailendra Singh; Sachdeva, Sandeep; Misra, Sunil Kumar; Agarwal, Prashant (National Journal of Community Medicine, 2018)
Background: Development during the early childhood, especially from fetus to two-year-old, is crucial in determining the nutrition, health and productivity status in the whole life course. The study was conducted to assess the developmental milestones’ achieve- ment of the children under study and also to find the association any between nutritional status and developmental achievement. Material & methods: A cross sectional community based study was conducted among under 5 years age children, in an urban slum of Agra. Nutritional status was assessed and classified as per WHO 2006 Growth Standards. Developmental Milestone Chart (DMC) was used to assess the childhood developmental status. Results: Overall 12.2 % of the children were found to be develop- mentally delayed. Prevalence of developmental delay increased significantly from infancy (0-11 months) (5.7 %) to 12-23 months of age, peaking at 12-23 months age (20.3 %), thereafter showing a decreasing trend to 15.3 % as the age of the child increased to more than 2 years. There was a close positive link observed between the nutritional status of the children and their development status. Mothers' education and low birth weight of the child were found to be significant influences on children's development. Conclusion: Childhood nutrition has received due attention, but the overall development of the child needs more focus.